Who is the red hulk ebook - Loeb, Jeph (Hulk Modern Era Epic Collection., 2024)
Hulk (2008) #1-12, King-Size Hulk #1, And Material From Incredible Hulk (2000) #600 And Wolverine (2003) #50. Red alert! There's a sadistic new red-skinned Hulk in the Marvel Universe, with keen intelligence and a radioactive touch! Who or what is he? And with Marvel's heroes powerless against him, will it take a Hulk to catch a Hulk? It's an explosive battle as the red and green Hulks collide! But even as a pack of wild Wendigos attacks Bruce Banner, She-Hulk recruits a cavalry of super heroines including Valkyrie, Thundra, Ms. Marvel and Storm! Plus: The Defenders reassemble to take down the Red Hulk, but he's got a team of his own! All this and a shock ending that changes the Hulk's life forever! Guest-starring Iron Man, Thor, Moon Knight, Spider-Man, Doc Samson, Rick Jones and Norman Osborn!